2015
DOI: 10.1038/onc.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Decoy receptors block TRAIL sensitivity at a supracellular level: the role of stromal cells in controlling tumour TRAIL sensitivity

Abstract: Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a death ligand cytokine known for its cytotoxic activity against malignantly transformed cells. TRAIL induces cell death through binding to death receptors DR4 and DR5. The inhibitory decoy receptors (DcR1 and DcR2) co-expressed with death receptor 4 (DR4)/DR5 on the same cell can block the transmission of the apoptotic signal. Here, we show that DcRs also regulate TRAIL sensitivity at a supracellular level and thus represent a mechanism by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 42 publications
1
54
0
Order By: Relevance
“…The structural optimization described here could potentially also be applied for death receptor (DR4/DR5) selective TRAIL variants in order to avoid competition with decoy receptors that could affect the efficacy of TRAIL-based therapies. 43 A possible approach combining such receptor-selective mutations with our refined concept for single-chain TRAIL described here could lead to the development of novel TRAIL-based therapies in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…The structural optimization described here could potentially also be applied for death receptor (DR4/DR5) selective TRAIL variants in order to avoid competition with decoy receptors that could affect the efficacy of TRAIL-based therapies. 43 A possible approach combining such receptor-selective mutations with our refined concept for single-chain TRAIL described here could lead to the development of novel TRAIL-based therapies in oncology.…”
Section: Discussionmentioning
confidence: 99%
“…However, TRAIL was engineered in order to escape from binding to DcRs, which were found to still exert trans-cellular regulation originating from stromal cells and affect tumor cells. Therefore, it is important to target these decoy receptors selectively to gain maximum efficacy [106]. Another recent study showed that DR4 and DR5 were upregulated while DcR1 and DcR2 downregulated in colon cancer cells after their treatment with a non-steroidal anti-inflammatory drug.…”
Section: Fas Cell Surface Death Receptor and Fas Ligandmentioning
confidence: 99%
“…Ubiquitous DcR1 (but not DcR2) expression has also been reported in the tumor-surrounding stroma of various cancers including breast, liver, pancreatic, ovarian, and prostrate (101). While deficient mTRAIL-R expression in mice promotes metastasis (102), it is not known if DcR1 and/or DcR2 can lend similar properties to tumors.…”
Section: Death Receptor Signaling In Tumor Immune Escapementioning
confidence: 99%
“…The importance of receptor selectivity has been recognized for some time and selective agonists against the TRAIL DRs either in form of agonistic antibodies or engineered ligand variants have been developed (101, 152). The ability of these agonists to fully replicate the receptor-activation mechanisms of the membrane-bound native ligand, however, has not been fully elucidated yet.…”
Section: Targeting Death Receptor Signaling For Anticancer Therapymentioning
confidence: 99%